Heranças portuguesas na poética de Cora Coralina - Silva, Eulidiane Morais da (2024)
Cora Coralina is one of the most important poets of Brazilian Literature. Her poetry is permeated by her affections, memories and beliefs; it is rich in historical-cultural and religious heritage. Among these legacies, those of Portuguese origin stand out because, in addition to Brazil being colonized by the Portuguese, the poet directly descends from them. Thus, the aim of this work is to analyze how the Portuguese heritage of this author materialize in her poems, considering the following theoretical assumptions: the poetic concepts of Emil Staiger, Octavio Paz, Alfredo Bosi and Jean Cohen; the contributions of Caio Prado Jr. and Alfredo Bosi to the historical context of the colonization process in our country; the concept of memory by Maurice Halbwachs and Aleida Assmann; and the concept of affection by Antonio Imbasciati and Sigmund Freud. To develop this work, it will be analyzed the poems from her first book Poemas dos becos de Goiás e estórias mais to identify references to these legacies, examine how they participate in both the construction of materiality and the meaning of her poems, how they dialogue with each other and with other ideas and constructions, and which of them has the greatest influence on this poetic work in order to deepen our understanding of her poetic creation.